Development of a patient‐centred conceptual framework of health‐related quality of life in neuromyelitis optica: a qualitative study. (24th November 2015) - Methley, Abigail M.; Mutch, Kerry; Moore, Perry; Jacob, Anu
Abstract: Background: Neuromyelitis optica (NMO) is an auto‐immune disease that can cause severe visual and mobility impairments. Research on health‐related quality of life (HRQoL) in NMO is scarce, limiting knowledge on factors influencing HRQoL and support needs. Aim: This study provides the first qualitative exploration of HRQoL in NMO, conducted to provide a conceptual framework for the development of an NMO patient‐reported outcome measure. Method: Fifteen people with NMO (aged 18–74; 11 women, 4 men) participated in semi‐structured interviews; data were analysed using constant comparative analysis. Results: HRQoL in NMO is a multifaceted concept incorporating highly subjective perceptions of normality and meaning. Four major themes were identified: impact of physical symptoms on daily living, utilizing support to achieve independence, expectations for life and meaningful roles in life and purpose. Discussion: Themes highlighted the importance of perceived normality, and its relationship to attaining life goals comparable to peers, as underpinning evaluations of HRQoL. Many people with severe disability reported a high HRQoL, suggesting the inappropriateness of assuming a negative HRQoL on the basis of an individual's neurological impairment. Conclusions: These findings further the conceptual understanding of HRQoL in NMO, informing patient‐care approaches and the development of an NMO‐specific patient‐reported outcome measure.